If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Log(3)(2x) = 9 Remove parenthesis around (2x) goL * 3 * 2x = 9 Reorder the terms for easier multiplication: 3 * 2goL * x = 9 Multiply 3 * 2 6goL * x = 9 Multiply goL * x 6goxL = 9 Solving 6goxL = 9 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by '6oxL'. g = 1.5o-1x-1L-1 Simplifying g = 1.5o-1x-1L-1
| 4(7x+6)=-144 | | 2+6-3q=1*2 | | (4n+1)(4n-1)=0 | | 1+6-3q=1*1 | | 0+6-3q=1*0 | | 4-2(x+3)=2x+6 | | 6-3q=1 | | x=3(0.6x) | | 6a=4a+9 | | x=2(8.0x) | | x=7(2.5x) | | x=10(3.2x) | | y/5-1x20 | | (x^8+5)*(x^12+7)=0 | | 2s=700 | | y/5-1x15 | | 3(3x-7)=26 | | 5x+18=3x+32 | | 2≥y/5−1 | | (2-5x)x(x-6)x(x+1)=0 | | 9x=642 | | (2-5x)*(x-6)*(x+1)=0 | | 2(-3)+6=0 | | (x^8+5)x(x^12+7)=0 | | (x^8+5)(x^12+7)=0 | | 28x+6=5x-40 | | 41/2x161/2÷41/2 | | X+4.5=104.8 | | 4x+4x=-8+14x | | 8sin^3x-6sinx+1=0 | | (2-5x)(x-6)(x+1)=0 | | -4x+7=9x |